Mechanical properties and joinability of the near-eutectic aluminium casting alloy AlSi12 - Neuser, Moritz; Holtkamp, Pia Katharina; Hoyer, Kay-Peter; Kappe, Fabian; Yildiz, Safak; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (The Journal of Materials: Design and Applications, Part L)
One of the most important strategies for reducing CO2 emissions in the mobility sector is lightweight construction. In particular, the car body offers several opportunities for weight reduction. Multi-material designs are increasingly being applied to select the most suitable material for the respective load and ultimately achieve synergy effects. For example, aluminium castings are used at the nodes of a spaceframe body. Subsequently, these are joined with profiles to form the bodyshell. To join different materials mechanical joining techniques, such as semi-tubular self-piercing riveting, are deployed. According to the current state of the art, cracks occur in the aluminium castings during the mechanical joining process as a result of the high degree of deformation. Although the aluminium casting alloys of the AlSi-system exhibit low ductility, these alloys reveal excellent castability. In particular, the ability to cast thin structural parts is enabled by the low liquidus point of the near eutectic aluminium casting alloys. This study addresses the mechanical joining properties of the near eutectic aluminium casting alloy AlSi12, depending on different microstructures. These are achieved by annealing processes and modifying agents. Through an adapted heat treatment, the previously lamellar morphology can be transformed into a globular morphology, which leads to increased ductility and prevents the formation of cracks during the self-piercing riveting (SPR). The joinability is investigated using different die geometries, whereas the joint formation is analysed regarding crack initiation. To evaluate the increased ductility, microstructural and mechanical tests are performed and finally, a microstructure-joinability correlation is established.
Keywords: aluminium; casting; microstructure; joinability; self-piercing riveting

Analysis of the binding mechanisms depending on versatile process variants of self-piercing riveting - Lüder, Stephan; Holtkamp, Pia Katharina; Wituschek, Simon; Bobbert, Mathias; Meschut, Gerson; Lechner, Michael; Schmale, Hans Christian (Materials Research Proceedings)
The constantly increasing demand for climate protection and resource conservation requires innovative and versatile joining processes that improve adaptability to the joining task and robustness to enable flexible manufacturing on a production line. Therefore, the versatile SPR (V-SPR) and tumbling SPR (T-SPR) were developed. Using the example of a mixed material combination HCT590X+Z (t0 = 1.0 mm) / EN AW-6014 T4 (t0 = 2.0 mm), these processes were examined and compared with regard to the binding mechanisms form closure and force closure using micrographs, non-destructive resistance measurements and destructive torsion tests. For this purpose, a new sample geometry was defined, and the methods were adapted to the SPR process variants.
Keywords: Joining; Self-Piercing Riveting; Sheet Metal

Investigation of the impact of a rotationally superimposed punch stroke on the binding mechanisms of a clinched joint - Lüder, Stephan; Wolf, Eugen; Schmale, Hans Christian; Brosius, Alexander (MATEC Web of Conferences)
This paper examines the impact of a rotationally superimposed punch stroke on the binding mechanisms of clinched joints of aluminum sheets. As part of the development of a method for ensuring the versatility of clinching, an additional rotational movement of the punch was introduced as a control variable to influence friction in the mechanical joining process. The effect of rotational superimposition on the force-displacement curve of the clinching processes was investigated using four test variants with different kinematics. The primary objective was to evaluate the binding mechanisms that maintain the integrity of the clinched joint. To evaluate the force closure of the resulting joint, two testing methods were employed throughout the course of the research, non-destructive resistance measurement using four-wire sensing method and destructive torsion testing. A crucial factor influencing the efficacy of the process is surface cleanliness, as contaminants between joining partners can impede the effectiveness of the clinched joint. Therefore, all specimens were meticulously cleaned prior to experimentation. This method exhibits promising potential in creating clinched joints that align with the demands of flexible manufacturing environments.
Keywords: Joining; Sheet Metal; Tribology; Clinching

Experimental and numerical investigation of the influence of rolling-induced sheet metal deformation on SPR joints - Schlichter, Malte Christian; Harabati, Özcan; Ludwig, Jean-Patrick; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
Abstract. In the development of advanced lightweight automotive solutions, self-piercing riveting (SPR) offers the possibility of joining multi-material structures to fulfil a wide variety of requirements. With regard to the entire process chain, production-related pre-deformations of the parts to be joined can influence the geometric shape and load capacity of SPR joints. Various studies have investigated the influence of pre-stretched sheet materials, in the sense of pre-drawing processes, on the formation of SPR joints. The impact of pre-stretching sheet metals on the formation of their geometrical characteristics and the shear-tensile strength of SPR processes was observed [1]. Pre-rolled semi-finished products are also joined together in mixed material automotive structures, e.g. tailor rolled blanks. This work aims to investigate the influence of pre-rolled joining parts on the geometric formation and load-carrying capacity of SPR joints. For this purpose, sheets of metal are cold-formed using a rolling process to induce a defined strain-hardening state in the material and then joined in various combinations. As the degree of deformation increases, the rolling of samples can lead to minimal accumulation of damage in the sheet materials, which can influence the joint behaviour. The rolling process, as well as the subsequent joining process, are also investigated by FEM. The influence of pre-rolled semi-finished products on the strength of the SPR joints is investigated.

Material Parameter Identification for a Stress-State-Dependent Ductile Damage and Failure Model Applied to Clinch Joining - Friedlein, Johannes; Böhnke, Max; Schlichter, Malte; Bobbert, Mathias; Meschut, Gerson; Mergheim, Julia; Steinmann, Paul (Journal of Manufacturing and Materials Processing)
Similar to bulk metal forming, clinch joining is characterised by large plastic deformations and a variety of different 3D stress states, including severe compression. However, inherent to plastic forming is the nucleation and growth of defects, whose detrimental effects on the material behaviour can be described by continuum damage models and eventually lead to material failure. As the damage evolution strongly depends on the stress state, a stress-state-dependent model is utilised to correctly track the accumulation. To formulate and parameterise this model, besides classical experiments, so-called modified punch tests are also integrated herein to enhance the calibration of the failure model by capturing a larger range of stress states and metal-forming-specific loading conditions. Moreover, when highly ductile materials are considered, such as the dual-phase steel HCT590X and the aluminium alloy EN AW-6014 T4 investigated here, strong necking and localisation might occur prior to fracture. This can alter the stress state and affect the actual strain at failure. This influence is captured by coupling plasticity and damage to incorporate the damage-induced softening effect. Its relative importance is shown by conducting inverse parameter identifications to determine damage and failure parameters for both mentioned ductile metals based on up to 12 different experiments.
Keywords: ductile damage; stress-state dependency; failure; parameter identification; punch test; clinching

Developing a numerical modelling strategy for metallic pin pressing processes in fibre reinforced thermoplastics to investigate fibre rearrangement mechanisms during joining - Gröger, B.; Gerritzen, Johannes; Hornig, A.; Gude, M. (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
A numerical modelling strategy for the direct pin pressing process of metallic pins into continuous fibre-reinforced thermoplastic organosheets is developed. The joining process is performed above the thermoplast’s melting temperature, altering the initial material structure of the composite by fibre rearrangement, which in turn influences the load-bearing capacity of the joint. Therefore, the modelling strategy aims at predicting the resultant material structure after pin pressing. The modelling approach considers both the textile architecture and the process parameters (temperature, tool velocity). A sub-meso modelling framework for the fibres based on a multi-filament approach is used. The interaction between fibres and the thermoplastic melt, as well as the matrix flow, is modelled using the Arbitrary Lagrangian Eulerian method. This allows for the prediction of matrix-rich zones and fibre rearrangement around the pin. The promising results show a good agreement of the resultant material structure in terms of compaction and fibre volume content around the pressed pin. Characteristic parameters show an underestimation of the laminate thickness below the pin. Moreover, an evaluation method for evaluating the orientation changes of the virtual multi-filaments is developed and presented to observe and assess fibre rearrangement and fibre volume content in detail during the numerical process simulation. It can be seen that only fibres around the pin are displaced and not in the whole molten area. Furthermore, it can be observed in detail that the initial position of the fibres in relation to the pin determines whether the fibres are displaced in the in-plane or out-of-plane direction.

Direct parameter identification for highly nonlinear strain rate dependent constitutive models using machine learning - Gerritzen, Johannes; Hornig, Andreas; Winkler, Peter; Gude, Maik (ECCM21 - Proceedings of the 21st European Conference on Composite Materials)
Fiber reinforced plastics (FRP) exhibit strongly non-linear deformation behavior. To capture this in simulations, intricate models with a variety of parameters are typically used. The identification of values for such parameters is highly challenging and requires in depth understanding of the model itself. Machine learning (ML) is a promising approach for alleviating this challenge by directly predicting parameters based on experimental results. So far, this works mostly for purely artificial data. In this work, two approaches to generalize to experimental data are investigated: a sequential approach, leveraging understanding of the constitutive model and a direct, purely data driven approach. This is exemplary carried out for a highly non-linear strain rate dependent constitutive model for the shear behavior of FRP.The sequential model is found to work better on both artificial and experimental data. It is capable of extracting well suited parameters from the artificial data under realistic conditions. For the experimental data, the model performance depends on the composition of the experimental curves, varying between excellently suiting and reasonable predictions. Taking the expert knowledge into account for ML-model training led to far better results than the purely data driven approach. Robustifying the model predictions on experimental data promises further improvement.
Keywords: Direct parameter identification; Machine learning; Convolutional neural networks; Strain rate dependency; Fiber reinforced plastics; woven composites; segmentation; synthetic training data; x-ray computed tomography

A methodology for direct parameter identification for experimental results using machine learning — Real world application to the highly non-linear deformation behavior of FRP - Gerritzen, Johannes; Hornig, Andreas; Winkler, Peter; Gude, Maik (Computational Materials Science)

Charakterisierung des Verformungszustandes gleichartiger Stahl-Stahl-Clinchverbindungen durch Anwendung quantitativer Bildanalyse - Hollmer, Katharina; Kuczyk, Martin; Friedlein, Johannes; Mergheim, Julia; Steinmann, Paul; Zimmermann, Martina

Prozessüberwachte Eigenschaftseinstellung beim Clinchen der ausscheidungshärtbaren Aluminiumlegierung EN AW-6014 - Lüder, Stephan; Kalich, Jan; Oesterle, Hannes; Schmale, Hans Christian (Tagung Werkstoffprüfung 2024: Werkstoffe und Bauteile auf dem Prüfstand, Prüftechnik – Kennwertermittlung – Schadensvermeidung)
Die Wandlungsfähigkeit einer Prozesskette erfordert Fügeverbindungen mit gezielt einstellbaren mechanischen, elektrischen, thermischen oder chemischen Eigenschaften. Dieser Beitrag beschreibt die Untersuchungen, inwiefern beim Clinchen zweier Bleche aus der ausscheidungshärtbaren Aluminiumlegierung EN AW-6014 bereits auf Basis der Prozessüberwachung des Kraft-Weg-Verlaufs bzw. des sich daraus ergebenden Energieeintrags auf die mechanischen und elektrischen Eigenschaften der Fügeverbindung geschlossen werden kann. An einer ausgewählten Fügeaufgabe werden im Stufenversuch die gegenseitigen Abhängigkeiten der einzelnen Einflussgrößen sowie des Wärmebehandlungszustands aufgezeigt. Dabei wird zwischen den Bindemechanismen Formschluss und Kraftschluss unterschieden. Die Formschlusskomponente wird anhand der geometrischen Kenngrößen wie Bodendicke, Halsdicke und Hinterschnitt in Mikroskopieuntersuchungen an Schliffbildern und den mechanischen Eigenschaften der Fügeverbindung untersucht, die im Scherzug- und Kopfzugversuch bestimmt werden. Dazu erfolgt zudem die Charakterisierung der Versagensbilder. Zur Quantifizierung der Kraftschlusskomponente der Fügeverbindung werden das Losbrechmoment im Torsionsversuch und der elektrische Widerstand mittels Vier-Leiter-Methode ermittelt und korreliert.
Keywords: Clinchen; Aluminium; Stufensetzversuch; Bindemechanismus; Formschluss; Kraftschluss; Zugversuch; Torsionsversuch; Widerstandsmessung

Development of a friction model for the numerical simulation of clinching processes - Böhnke, Max; Bielak, Christian Roman; Beck, Robert; Bobbert, Mathias; Meschut, Gerson (Friction)

Material Parameter Identification for a Stress-State-Dependent Ductile Damage and Failure Model Applied to Clinch Joining - Friedlein, Johannes; Böhnke, Max; Schlichter, Malte Christian; Bobbert, Mathias; Meschut, Gerson; Mergheim, Julia; Steinmann, Paul (Journal of Manufacturing and Materials Processing)
Similar to bulk metal forming, clinch joining is characterised by large plastic deformations and a variety of different 3D stress states, including severe compression. However, inherent to plastic forming is the nucleation and growth of defects, whose detrimental effects on the material behaviour can be described by continuum damage models and eventually lead to material failure. As the damage evolution strongly depends on the stress state, a stress-state-dependent model is utilised to correctly track the accumulation. To formulate and parameterise this model, besides classical experiments, so-called modified punch tests are also integrated herein to enhance the calibration of the failure model by capturing a larger range of stress states and metal-forming-specific loading conditions. Moreover, when highly ductile materials are considered, such as the dual-phase steel HCT590X and the aluminium alloy EN AW-6014 T4 investigated here, strong necking and localisation might occur prior to fracture. This can alter the stress state and affect the actual strain at failure. This influence is captured by coupling plasticity and damage to incorporate the damage-induced softening effect. Its relative importance is shown by conducting inverse parameter identifications to determine damage and failure parameters for both mentioned ductile metals based on up to 12 different experiments.

A calibration method for failure modeling in clinching process simulations - Böhnke, Max; Bielak, Christian Roman; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)
Abstract. In the numerical simulation of mechanical joining technologies such as clinching, the material modeling of the joining parts is of major importance. This includes modeling the damage and failure behavior of the materials in accordance with varying occurring stress states. This paper presents a calibration method of three different fracture models. The calibration of the models is done by use of experimental data from a modified punch test, tensile test and bulge test in order to map the occurring stress states from clinching processes and to precisely model the resulting failure behavior. Experimental investigations were carried out for an aluminum alloy EN AW-6014 in temper T4 and compared with the simulative results generated in LS-DYNA. The comparison of force-displacement curves and failure initiation shows that the Hosford–Coulomb model predicts the failure behavior for the material used and the tests applied with the best accuracy.

Influence of plastic orthotropy on clinching of sheet metal - Friedlein, Johannes; Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)

Numerical Investigation of the Coupled Friction Behavior in the Clinching Process Chain - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Lecture Notes in Mechanical Engineering)

Efficient gradient enhancements for plasticity with ductile damage in the logarithmic strain space - Friedlein, Johannes; Mergheim, Julia; Steinmann, Paul (European Journal of Mechanics - A/Solids)
We contrast different gradient-enhancements for plasticity-damage material models in the logarithmic strain space and compare them to reference models based on multiplicative plasticity. The models being compared include plasticity - gradient-damage, where the gradient-enhancement is applied on the local damage variable, and gradient-plasticity - damage with a gradient-enhanced plastic hardening variable. Thereby, gradient-plasticity proved to be able to simultaneously regularise plastic and ductile (plasticity-driven) damage localisation as confirmed by numerical localisation analyses. This appears to be especially advantageous for logarithmic strain space plasticity-damage, because of the observed plastic localisation even for the case of plasticity with hardening. Even though gradient-plasticity appears to be numerically more demanding, two numerical examples indicate a good robustness and mesh objectivity in the softening regime. Moreover, the internal length for plasticity is able to adjust the damage zone width, similarly to gradient-damage, however ensuring a priori that damage takes place exclusively inside the plastic zone.
Keywords: Finite plasticity; Logarithmic strain space; Ductile damage; Gradient-enhancement; Gradient-plasticity; Gradient-damage; Loss of ellipticity

Modelling of Composite Manufacturing Processes Incorporating Large Fibre Deformations and Process Parameter Interactions - Example Braiding - Gröger, Benjamin; Gerritzen, Johannes; Eckardt, Simon; Gelencsér, Anton; Kunze, Eckart; Hornig, Andreas; Protz, Richard; Gude, Maik

Thermomechanical Joining of Hypoeutectic Aluminium Cast Plates - Borgert, Thomas; Neuser, Moritz; Hoyer, Kay-Peter; Homberg, Werner; Schaper, Mirko (Journal of Manufacturing and Materials Processing)
Consistent lightweight construction in the area of vehicle manufacturing requires the increased use of multi-material combinations. This, in turn, requires an adaptation of standard joining techniques. In multi-material combinations, the importance of integral cast components, in particular, is increasing and poses additional technical challenges for the industry. One approach to solve these challenges is adaptable joining elements manufactured by a thermomechanical forming process. By applying an incremental and thermomechanical joining process, it is possible to react immediately and adapt the joining process inline to reduce the number of different joining elements. In the investigation described in this publication, cast plates made of the cast aluminium alloy EN AC-AlSi9 serve as joining partners, which are processed by sand casting. The joining process of hypoeutectic AlSi alloys is challenging as their brittle character leads to cracks in the joint during conventional mechanical joining. To solve this, the frictional heat of the novel joining process applied can provide a finer microstructure in the hypoeutectic AlSi9 cast alloy. In detail, its Si is finer-grained, resulting in higher ductility of the joint. This study reveals the thermomechanical joining suitability of a hypoeutectic cast aluminium alloy in combination with adaptively manufactured auxiliary joining elements.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Methoden zur Charakterisierung der Bindemechanismen bei geclinchten elektrischen Kontakten - Reschke, Gregor; Kalich, Jan; Füssel, Uwe (Tagung Werkstoffprüfung 2022: Werkstoffe und Bauteile auf dem Prüfstand, Prüftechnik – Kennwertermittlung – Schadensvermeidung)
Das umformtechnische Fügeverfahren Clinchen ermöglicht ein energiearmes Fügen von Blechen und dient traditionell der Übertragung mechanischer Kräfte. Neue Einsatzgebiete erfordern eine elektrische oder thermische Leitfähigkeit, sodass es notwendig ist, das Clinchen entsprechend zu qualifizieren. Es wurden Untersuchungen an Aluminiumverbindungen durchgeführt, welche mit hohen Kurzzeitströmen belastet wurden. Der Einfluss verschiedener Oberflächenvorbehandlungen wurde betrachtet. Als Charakterisierungsmethode für die Bauteile und die geclinchten Fügeverbindungen wird die Messung des elektrischen Widerstandes herangezogen. Die untersuchten Clinchverbindungen sind fähig, die im Fehlerfall auftretenden Kurzzeitströme zu übertragen. Der Oberflächenzustand übt dabei einen signifikanten Einfluss auf die Clinchpunktausbildung und damit auf deren elektrische Eigenschaften aus. Durch Messung des elektrischen Widerstandes vor und nach dem Fügen sowie nach einer Bestromung mit Fehlerströmen, kann das Kontaktverhalten qualifiziert werden.
Keywords: Clinchen; Bindemechanismen; elektrische Eigenschaften; Aluminium; Kurzzeitbestromung

Numerical analysis of failure modeling in clinching process chain simulation - Bielak, Christian Roman; Böhnke, Max; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)
The application of the mechanical joining process clinching allows the assembly of different sheet metal materials with a wide range of material thickness configurations, which is of interest for lightweight multi-material structures. In order to be able to predict the clinched joint properties as a function of the individual manufacturing steps, current studies focus on numerical modeling of the entire clinching process chain. It is essential to be able to take into account the influence of the joining process-induced damage on the load-bearing capacity of the joint during the loading phase. This study presents a numerical damage accumulation in the clinching process based on an implemented Hosford-Coulomb failure model using a 3D clinching process model applied on the aluminum alloy EN AW-6014 in temper T4. A correspondence of the experimentally determined failure location with the element of the highest numerically determined damage accumulation is shown. Moreover, the experimentally determined failure behavior is predicted to be in agreement in the numerical loading simulation with transferred pre-damage from the process simulation.